Language strategies and consumer influence: socio-linguistic features of advertising - Kholboboyeva , Aziza (The Lingua Spectrum, 2025)
Sociolinguistics in advertising discourse examines how language is used in advertising to convey messages, shape consumer behavior, and reflect or reinforce societal norms, values, and identities. It involves analyzing the ways in which language choices – such as vocabulary, tone, accent, register, and cultural references – are strategically employed to appeal to specific social groups or create particular meanings. In this context, sociolinguistics helps to explore how language functions in the intersection between communication, culture, and society. Sociolinguistics offers valuable insights into how language functions in advertising, revealing how advertisements construct and communicate meanings that resonate with diverse social groups. By understanding how language shapes identity, appeals to emotions, and reinforces cultural norms, advertisers can craft more effective and targeted campaigns. At the same time, sociolinguistic analysis helps uncover the implicit messages and power dynamics embedded in advertising discourse, revealing how consumer culture is constructed through language. This article analyzes theoretical views on the representation of sociolinguistic aspects in advertising discourse.